A comparative study to evaluate the optimum intubating dose of rocuronium bromide versus succinylcholine chloride as an ideal intubating muscle-relaxing agent - Bhunia, Pratibha; Mandal, Anupama; Chatterjee, Subhrangsu; Mayur, Nairita (Asian Journal of Medical Sciences, 2024)
Background: Rocuronium bromide is a new amino steroidal neuromuscular blocking agent which is structurally related to vecuronium and its onset time and intubating conditions are comparable with succinylcholine and without the undesirable side effects. Aims and Objectives: This study was planned to evaluate the ideal intubating dose of rocuronium bromide by comparing intubating conditions achieved by its different doses of rocuronium bromide and to consider rocuronium as an ideal intubating muscle relaxing agent, in place of succinylcholine chloride for elective long surgeries. Materials and Methods: This study was conducted on 120 patients who fulfilled the eligibility criteria. These patients were randomized into four groups of 30 each by block randomization technique. Each group received rocuronium bromide 0.6 mg/kg, 0.9 mg/kg, 1.2 mg/kg, and succinylcholine chloride 1 mg/kg, respectively. Results: Out of all the three doses of rocuronium bromide 0.9 mg/kg produced a similar intubating condition as succinylcholine chloride in the dose of 1 mg/kg without undue prolongation of the neuromuscular blockade. Conclusion: Rocuronium bromide can be used as an alternative to succinylcholine as an ideal intubating muscle relaxing agent.